Molecular and physiological characterization of mono- and dicarboxylic acids permeases in the yeast Kluyveromyces lactis - Queirós, Odília (2003)
Poster apresentado em XXI International Conference on Yeast Genetics and Molecular Biology, Gotemburgo, Suécia, 7 Jul. - 12 Jul. 2003